Pengaruh Pajak, Ukuran Perusahaan, dan Mekanisme Bonus Terhadap Transfer Pricing - Salshabila Azhari; Sri Putri Winingrum (ITB AAS INDONESIA, 2024)
This study aims to analyze and obtain empirical evidence of the effect of tax, company size, and the bonus mechanism on transfer pricing. The type of research used is descriptive quantitative. The population of this study are energy sector companies listed on the Indonesia Stock Exchange in 2017-2021. Selection of this sample using purposive sampling method. The amount of data obtained was 45 data. The data analysis method used is multiple linear regression which was processed using Eviews 12. The results of this study simultaneously show that taxes, firm size, and the bonus mechanism have an influence on ricing transfers. And partially shows that the tax and bonus mechanisms have no effect on transfer pricing, while company size has an effect on transfer pricing.